Conservation of a lateralized visuomotor axis in hawkmoth proboscis probing - Lochlan Walsh; Sören Magnus Kannegieser; Anna Lisa Stöckl (Proceedings of the National Academy of Sciences, 2026)
Lateralization of behavior, including motor control and sensory processing, is widespread across bilaterians. In visually guided tasks it often manifests as an axis aligning eye, appendage, and a target within a shared reference frame, such as eye-hand coordination in humans or eye-beak coordination in birds. While studied intensively in a few vertebrate systems, whether similar control principles apply to invertebrates, and more generally, how sensory and motor lateralization are linked mechanistically, remains unclear. Using the proboscis inspection behavior of hummingbird hawkmoth Macroglossum stellatarum as a model for visual appendage guidance, our study provides evidence for lateralized visuo-motor control in an invertebrate. Combining high-speed videography and markerless pose estimation, we establish the underlying control axis between the hawkmoths’ unpaired appendage and its eye. We demonstrate that individuals displayed stable, idiosyncratic proboscis lateralization, which was tightly linked to their instantaneous viewing angle of visual targets, thus forming a persistent eye–proboscis–target axis. This axis also had functional consequences for feature-targeting. Assessing the sensory–motor plasticity using monocular occlusion, we found that moths preserved their lateralized visuo-motor geometry by adjusting body posture during flower inspection. Our findings suggest convergent control principles with vertebrate models of lateralized visual appendage guidance, while highlighting stark differences in sensory–motor plasticity, thus adding to our general understanding of how lateralization shapes control strategies across nervous systems.